2019
DOI: 10.29359/bjhpa.11.2.08
|View full text |Cite
|
Sign up to set email alerts
|

Selected aspects of testing the positioning accuracy of GNSS receivers used in sports and recreation by dynamic measurements

Abstract: Background: Satellite navigation systems have been used in professional navigation and geodesy for many years. The past decade has been a time of extending their application to devices also accessible to non-professional users. Sports and recreation is one of the major new areas in which satellite receivers are used. Since device manufacturers do not inform precisely (or at all) about the level of the positioning accuracy provided by such devices, it is necessary to propose a method of its assessment. This pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This frequency is commonly adopted for the recording of tracks in the majority of currently manufactured sport and recreation receivers (including those used for running and cycling). In the context of analyses described in publications [80,81], the frequency of 1 Hz appears to be adequate for monitoring a run over a distance of 2000 m.…”
Section: Test Receivers and The Test Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…This frequency is commonly adopted for the recording of tracks in the majority of currently manufactured sport and recreation receivers (including those used for running and cycling). In the context of analyses described in publications [80,81], the frequency of 1 Hz appears to be adequate for monitoring a run over a distance of 2000 m.…”
Section: Test Receivers and The Test Proceduresmentioning
confidence: 99%
“…On the other hand, in [65][66][67] authors used their own measures. The right approach to measures can be found in publications [68]-CEP, DRMS and 2DRMS measures, in [69][70][71]-RMS, DRMS, 2DRMS, CEP, R68, R95 and SEP measures. It can also be observed that there are studies under different field conditions, which have a decisive influence on the positioning accuracy by GNSS receivers.…”
Section: Introductionmentioning
confidence: 99%
“…(a) Predicted accuracy-the accuracy of position determination by the system relative to the actual values; (b) Repeatable accuracy-the level of accuracy that allows the user to return to the coordinates determined earlier by the same system; (c) Relative accuracy-the ability to measure (determine) the coordinates relative to a different user within the same system at the same time [13].…”
mentioning
confidence: 99%